The moral values of the families of the reading book for the sixth grade of primary school (Journal of the College of Basic Education, 2023)
The study of values comes from its close connection with all the principles of social, economic and political lifeIt is related to human relations in all its forms. Educators emphasized the importance of moral values and their role in educationEvery human activity» as its importance and role in modern education increased in light of the scientific and progressive progressWho invaded all the principles of life and who did not solve the problems of contemporary human life, but rather increased tensionsand social and political unrest due to its failure to provide an optimal alternative to these ethical valuesabsent in the real world. The importance of moral values in the life of the individual and society is clear because behaviorIn its essence, it is based on the principle of the system that governs relations between people and achieves harmony between peopleThe individual and the social environment he deals with in any age group.Perhaps the importance of ethics stems from its close relationship with all the principles of life »for the sake of notdeviates from the right path and we make the school the first ally of the family to reach this resultBecause education is an important factor of change and social advancement, especially in our Arab and Muslim societyIts basis is moral values, as the Messenger said: [I was sent to complete the honorable morals].There is no doubt that family education is one of the basic responsibilities of the family, as the family is the factoryThe first that forms the personality of the social being, especially in the early stages of his life.The first thing that the direction of inculcating and developing values calls for is defining the areas of values that should be taughtIn the school and the selection of educational means and methods that help learners to represent and acquire those valuesIn recent times, there have been many calls for the need for educational institutions to play a greater role in educationThe field of moral education and giving it more space in the educational curricula.